Genetic relationships among strains of Xanthomonas axonopodis pv. punicae based on random amplified polymorphic DNA PCR - A.M. Mishra, K.K. Suryawanshi, S.G. Borkar and (Indian Phytopathology, 2016)
The bacterial blight of pomegranate (Punica granatum L.) caused by Xanthomonas axonopodis pv. punicae is a serious and major disease in pomegranate cultivation in India. In present investigation characterization of 23 isolates of Xanthomonas axonopodis pv. punicae (Xap) collected from different geographical locations in India were done at molecular level using random decamer primers. The primers OPA-01, OPA-02, OPA-06, OPA-09, OPB-03, OPB-04, OPB-07, OPF-07 and OPF-09 were found most significant and polymorphic. Percent polymorphism among these isolates was 89.32 and average no of polymorphic bands per primer was 3.33. The dendrogram analysis based the dendrogram based on RAPD fingerprint data revealed 2 major clusters among 23 isolates of this pathogen. The dice similarity coefficient values among Xap isolates ranged from 0.11 to 0.96. Maximum similarity value of 0.96 was noticed in between Tamil Nadu isolate TEGG-17 and Andhra Pradesh isolate AM -18. There was low similarity coefficient of 0.11 noticed in between Nashik isolate MNSN-03 and Solapur isolate MSMM-08.